Are habits important for the propagation of business cycle fluctuations in Bulgaria? - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
We introduce internal consumption habits into a real-business-cycle setup augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of the presence of internal consumption habits motive for the propagation cyclical fluctuations in Bulgaria. Allowing for habits in consumption improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework without habits, e.g., Vasilev (2009).
Keywords: E32; E37; 330; Business cycles; consumption habits; Bulgaria